Potensi Lengkong Culinary Night Sebagai Daya Tarik Wisata - Rizkyatul C, Adinda; Swaratika, Lugina; Nurihzany, Nazwa; Shafa M, Rivita; Karbelani H, Zaenab; Rozak, Rama Wijaya Abdul; Sukriyah, Erry (Program Studi Pariwisata Program Sarjana, Fakultas Pariwisata, Universitas Udayana, 2023)
Lengkong Culinary Night has become one of the popular tourist attractions due to its diverse culinary offerings. This research focuses on the potential of culinary tourism as a tourist attraction. The research aims to serve as a reference for readers to explore the potential of a place as a tourist attraction. The research methodology used in this study is qualitative and descriptive, and data collection techniques include observation, interviews, and documentation. The participants in this study include managers, vendors, and visitors. The data collected is analyzed and described based on the 4A aspects of the tourist attraction and a SWOT analysis is conducted. The results indicate that there is great potential for culinary tourism to be developed as a tourist attraction, and sustainable culinary tourism development can be applied. Keywords: Potensi Wisata, Wisata Kuliner, Culinary Night, Atraksi Wisata, Lengkong Culinary Night